Exploiting the furo[2,3-b]pyridine core against multidrug-resistant Mycobacterium tuberculosis - Fumagalli, Fernando; de Melo, Shaiani Maria Gil; Ribeiro, Camila Maríngolo [UNESP]; Solcia, Mariana Cristina [UNESP]; Pavan, Fernando Rogério [UNESP]; da Silva Emery, Flavio [UNESP] (Elsevier, 2019)
Identification of new antibiotics suitable for the treatment of tuberculosis is required. In addition to selectivity, it is necessary to find new antibiotics that are effective when the tuberculous mycobacteria are resistant to the available therapies. The furo[2,3-b]pyridine core offers potential for this application. Herein, we have described the screening of our in-house library of furopyridines against Mycobacterium tuberculosis and identified a promising selective bioactive compound against different drug-resistant strains of this mycobacteria. The library of compounds was prepared by a C–H amination reaction using mild and metal-free conditions, increasing the available information about the reactivity of furo[2,3-b]pyridine core through this reaction.
Keywords: Antibiotic; C–H activation; Furopyridine; Multidrug-resistant; Tuberculosis